2021
DOI: 10.3390/antiox10060950
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Oxidative Stress in Glioblastoma Multiforme Following Treatment with Purine Derivatives

Abstract: Recently, small compound-based therapies have provided new insights into the treatment of glioblastoma multiforme (GBM) by inducing oxidative impairment. Kinetin riboside (KR) and newly designed derivatives (8-azaKR, 7-deazaKR) selectively affect the molecular pathways crucial for cell growth by interfering with the redox status of cancer cells. Thus, these compounds might serve as potential alternatives in the oxidative therapy of GBM. The increased basal levels of reactive oxygen species (ROS) in GBM support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 106 publications
1
11
0
Order By: Relevance
“…These results are consistent with that of Barros, who showed that higher respiratory activity decreases the release of mitochondrial ROS and increases lifespan in S. cerevisiae [64]. Studies on human cells have shown that enhanced SRC is associated with a readiness to meet an extra energy demand and reduced ROS generation [19,65]. Recently, flavonoids from sacred lotus stamen extracts were shown to extend CLS by maintaining MMP and reducing the level of ROS [66].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are consistent with that of Barros, who showed that higher respiratory activity decreases the release of mitochondrial ROS and increases lifespan in S. cerevisiae [64]. Studies on human cells have shown that enhanced SRC is associated with a readiness to meet an extra energy demand and reduced ROS generation [19,65]. Recently, flavonoids from sacred lotus stamen extracts were shown to extend CLS by maintaining MMP and reducing the level of ROS [66].…”
Section: Discussionsupporting
confidence: 89%
“…Among these compounds, cytosine arabinoside (cytarabine) is the most widely used in the treatment of leukemias (WHO). Another compound, 6-Furfuryladenine (kinetin), has been shown to promote healthy aging [18], while N-6-Furfuryladenosine (kinetin riboside) and its derivatives were proven to be selective anticancer agents [19]. Preliminary results obtained from our experiments with human cell lines (unpublished data) indicated that FC exhibits promising biological activities, such as the stimulation of proliferation, ROS scavenging, or the enhancement of mitochondrial function, which together could have a potential antiaging effect.…”
Section: Introductionmentioning
confidence: 83%
“…Earlier studies have also reported favorable associations between adherence to healthy plant-based diets and risk of breast cancer 21 , non-alcoholic fatty liver disease 22 , and psychological disorder 23 . During glioma progression, reactive oxygen species (ROS) are activated and resulting in oxidative stress (OS) 24 . To avoid oxidative stress, these ROS can be inactivated by antioxidants like glutathione, vitamin E, beta carotene, and vitamin C 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Kinetin riboside (KR) and newly created derivatives (8-azaKR and 7-deazaKR) interfere with the redox state of cancer cells by selectively affecting molecular pathways essential for cell proliferation. KR and 7-deazaKR are efficient anticancer drugs and could be attractive options for oxidative therapy, concentrating on the cellular redox conditions of GBM cells and the inducement of apoptosis, according to previous findings [ 62 ]. The SW1088 glioma line showed no ROS induction despite incubation with 2-ME; however, it induced RNS across the entire concentration range of the compound at both physiologically and pharmacologically relevant concentrations, and in addition, it upregulated nNOS expression.…”
Section: Discussionmentioning
confidence: 99%